New species and new records of black fungus gnats (Diptera: Sciaridae) from the Viidumäe Nature Reserve, Estonia - Menzel, Frank; Salmela, Jukka; Vilkamaa, Pekka (European Journal of Taxonomy, 2020)
An inventory of Sciaridae (Diptera: Sciaroidea) from a eutrophic fen and a spring brook in Viidumäe Nature Reserve (Estonia, Saaremaa Island) recorded a total of 60 species, of which 57 are new records for Estonia, including two that are new to science and described herein as Cratyna (Diversicratyna) palustricola sp. nov. (Estonia) and Sciara bryophila sp. nov. (Estonia, Finland). This has raised the number of Sciaridae known from Estonia from 6 to 63.